Spor fra Ørsted. Tværfaglige forsknings- og formidlingsperspektiver fra Det Kgl. Biblioteks Ørsted-arkiv - Thomasen, Laura Søvsø (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2019)
Laura Søvsø Thomasen: Tracing Ørsted – Interdisciplinary Research and Dissemination Perspectives from the Royal Danish Library’s Hans Christian Ørsted Archive 2020 marks the 200th anniversary for Hans Christian Ørsted’s discovery of electromagnetism. In connection with the celebration of the bicentennial, the Royal Danish Library will publish online their entire Ørsted archive, which includes a substantial collection of letters to and from Ørsted, a large number of scientific papers on physics, chemistry and mathematics, as well as a plethora of different works on everything from language over politics to aesthetics. With the digitalisation of the archive, the library has created a number of teaching materials available for students in the Danish upper secondary school that showcase the interdisciplinary methods and works by Ørsted but also emphasises the interdisciplinary work required by the students to solve the problem sets. In the article, I explore how the digitalisation of the Ørsted archive opens up for new perspectives both in academic research as well as didactic perspectives in relation to the teaching materials accompanying the archive. In terms of new research perspective, the Ørsted archive showcases how Ørsted not only was interested in a variety of subjects in and around both the natural and cultural sciences, but that he also was truly interdisciplinary himself. Through source material from the archive I show how when approached from the interdisciplinary fields ‘Literature and Science’ and ‘Visual Culture of Science’ that Ørsted integrated both illustrations and literary components to communicate his scientific arguments.